Evaluasi Program Paket C di Sanggar Kegiatan Belajar - Hartoyo, Hartoyo; Hamzah, Syukri; Hadiwinarto, Hadiwinarto (JOEAI (Journal of Education and Instruction), 2023)
This study aims to get an overview and at the same time evaluate the implementation of the Musi Rawas SKB Foster Package C Program. This type of research is an evaluation research that uses a quantitative approach supported by a qualitative approach. The evaluation model used is the CIPP model (context, input, process, product). Data collection was carried out through questionnaires, interviews, observations, and documentation with informants from learning residents, organizers, and tutors. The data analysis technique used is descriptive quantitative and qualitative techniques. The results of the study show that: (1) the level of community need for the Package C Program in SKB is high and most of the learning residents state that it is relevant to the learning needs of the community; (2) learning residents in terms of educational background and age have met the criteria, tutors and administrators in terms of educational background and experience have met the criteria; (3) the activities of learning residents in class and at home are quite good, although not optimal, the activities of tutors in learning in class are in the good category. Most of the learning residents state that they do not get skills education; and (4) the academic achievement of the learning residents in the form of an average odd semester score in 2022 is in the sufficient category, and almost all learning residents state that the Package C Program provides benefits. The conclusions based on the results of the study are that the needs of the learning community for Package C are classified as high, the characteristics of the tutor have met the criteria seen from their educational background and teaching experience, the infrastructure used is quite good. The majority of learning residents stated that the Package C Program at the Musi Rawas SKB was quite useful, namely being able to increase knowledge, skills, change the attitude/mental of learning residents, and open up opportunities to be able to continue higher education. Keywords: Learning Evaluation, Package C, Learning Activities